Silver-enhanced nucleation and morphology control of surface crystallized Ba0.5Sr0.5Zn2Si2O7 from 8 BaO·8 SrO·34 ZnO·50 SiO2 glass. Issue 15 (15th October 2019) - Kracker, Michael; Thieme, Christian; Thieme, Katrin; Höche, Thomas; Rüssel, Christian
Abstract: Glass samples were polished and coated with a 10 nm thick silver layer. Both, silver-coated and uncoated samples were thermally treated at 750 °C for 4 h or at 790 °C for 2 h. In both types of samples, the phase Ba0.5 Sr0.5 Zn2 Si2 O7 crystallized, which exhibits a negative thermal expansion. After thermal treatment, the uncoated sample showed a low number of crystals at the surface and even less if a crystallization temperature of 790 °C was supplied. By contrast, the silver-coated sample exhibited much more crystals at the surface. The number of crystals did not considerably depend on the crystallization temperature. The crystals in the silver-coated sample grew into the bulk with a highly unique orientation. Their crystallographic c-axes are perpendicular to the surface. The orientation of the crystals of the uncoated sample was not as strict. The uncoated sample showed numerous cracks, while the silver-coated sample did not show any cracks. In a first step, the metallic silver layer is dewetted and forms a structure composed by silver islands. During further heating, the islands are oxidized to Ag2 O, which diffuses in the glass. Since Ag2 O is incorporated in the glass as a network modifier, the network connectivity of the glass and hence also Tg decreases. This results in a higher nucleation rate in surface near regions.